Remaja Siaga : Kenali Bahaya Hiperglikemia Sejak Dini dan Cara Menanganinya pada Siswa SMK Nurul Ulum Lebaksiu - Cindy Eka Lestari; Anita Soraya; Aiza Amelia Surya Ningrat; Kholivia Tri Yuniati; Nayla Ade Shahira; Salwa Kusuma Dwi Athifah (Lembaga Pengembangan Kinerja Dosen, 2026)
Hyperglycemia is a condition of elevated blood sugar levels that can potentially lead to various health complications if not controlled early. This condition is often influenced by unhealthy eating habits, lack of physical activity, and low awareness among adolescents regarding regular blood sugar checks. Adolescents are an age group that is vulnerable to lifestyle changes, putting them at risk of developing metabolic disorders later in life. This community service activity aims to increase adolescent knowledge and awareness regarding the dangers of hyperglycemia and the importance of preventive measures from school age. The activity was carried out at SMK Nurul Ulum Lebaksiu, involving 59 students as participants. The methods used included health education through audio-visual media, interactive lectures, discussions, and Random Blood Sugar (GDS) tests for early detection. The results of the activity showed an increase in student knowledge based on a comparison of pre-test and post-test scores, as well as the implementation of GDS tests on all participants. This activity is expected to foster healthy lifestyle behaviors and increase adolescent awareness of the prevention of non-communicable diseases.